REENGINEERING OF OPEN SOFTWARE SYSTEM OF 3D MODELING BRL-CAD - Stanislav Velykodniy (Сучасний стан наукових досліджень та технологій в промисловості, 2019)
Computer Graphics is an up-to-date industry in the design and application of rapidly evolving computing systems. The subject of the work is designing a graphical user interface. The purpose of the work is to perform reengineering (evolutionary improvement while maintaining the positive qualities that are confirmed by the operation) of an open-source three-dimensional software system with inheritance of full functionality and principles of operation. BRL-CAD is a specialized open source cross-platform system that is a powerful 3D computer aided design system for bulk body modeling. The software system includes an interactive geometric editor, parallel ray tracing, rendering and geometric analysis. Objectives: To summarize the results of experimental studies at the level of representation of classes, components and use cases, which must be submitted using a unified modeling language – UML, with the processing and interpretation of results at the level of CASE-tool; to analyze the source code translation of the redesigned BRL-CAD graphical user interface. Methods. The process of designing or redesigning new software products is ineffective without using the UML methodology, but with its adherence – the speed of development is increased several times over.  In this paper, we use the UML 2.5 methodology using the Enterprise Architect 14.0 CASE toolkit. Results. The main focus is on three diagrams: classes, use cases and components. Based on these diagrams, code generators and programmers continue to work, while other (auxiliary) diagrams are intended to explain some of the complex specifications of the project, which does not, however, diminish their relevance within the project. The present study summarizes the results of experimental studies; source code translation results are analyzed and summarized, the main one being the reduction in the complexity of creating open source software using the BRL-CAD example. Conclusions. BRL-CAD is acceptable for the experienced designer, but for the beginner or student, its application process will be very complicated. A thorough analysis of the environment revealed the presence of two modules contained in the structure of the system that help the potential user to quickly design and model. Also fundamental to the package is the ability to support the design and analysis of visual models based on complex objects, consisting of a large set of graphic primitives. The powerful side of the system is the extraordinary speed of visual means, ray tracer and rendering. Compared to analogs, it can be state that the visualization process is one of the fastest among the existing ones.